Acute Cold Respiratory Syndrome: A Narrative Review of Pathophysiological Mechanisms Beyond Viral Etiology - Gozhenko, Anatoliy; Zukow, Walery; Biryukov, Viktor; Vitiukov, Oleksandr (Pedagogy and Psychology of Sport, 2026)
Background Acute respiratory illnesses, collectively referred to as the "common cold," represent one of the most prevalent conditions worldwide, affecting billions of individuals annually and imposing an enormous socioeconomic burden estimated at over $40 billion per year in the United States alone. Despite their ubiquity, the etiopathogenesis of these conditions remains insufficiently understood and scientifically contested. Contemporary medicine attributes all common cold episodes exclusively to viral infections — predominantly rhinoviruses (30–50%), coronaviruses (10–15%), and other respiratory viruses. However, this monocausal viral paradigm fails to explain several well-documented clinical and epidemiological inconsistencies: the onset of symptoms within minutes of cold exposure (far preceding any possible viral incubation period), the reversibility of symptoms upon rewarming, the absence of fever in a substantial proportion of cases, and the paradoxical age-related pattern of incidence in which elderly individuals — despite progressive immunosenescence — suffer fewer episodes than children or young adults. These unresolved contradictions call for a fundamental reassessment of the pathogenesis of cold-associated respiratory disease. Objective This narrative review critically examines the role of cold exposure and cold stress in the pathogenesis of acute upper respiratory tract disorders and proposes a novel conceptual framework — Acute Cold Respiratory Syndrome (ACRS) — as an independent nosological entity with clearly defined pathophysiological mechanisms, distinct diagnostic criteria, and specific clinical implications. The review further presents a paradigmatic shift from a pathogen-centric to a host-response model of the common cold, as proposed by Gozhenko et al. (2025). Methods A comprehensive narrative literature review was conducted across PubMed/MEDLINE, Scopus, Web of Science, and Google Scholar databases, covering publications from 1946 to 2025 in English, Ukrainian, and Polish. Search terms included: cold stress, thermoregulation, upper respiratory tract, mucosal immunity, vasoconstriction, common cold pathophysiology, mucociliary clearance, cold air inhalation, HPA axis immune suppression, TRPM8, TRPA1, nasal mucosa cold. Artificial intelligence tools (large language models) were used exclusively for auxiliary tasks — initial literature sorting, grammatical proofreading, and reference formatting — with all scientific content, analyses, and conclusions being the sole intellectual product of the authors. Original thermodynamic calculations of metabolic energy expenditure during cold air breathing were performed and are presented in full within the manuscript. Results Convergent evidence from physiology, immunology, neuroscience, and thermodynamics reveals five interconnected pathophysiological mechanisms underlying ACRS: Vascular dysfunction: Inhalation of cold air activates TRPM8 (threshold < 25–28°C) and TRPA1 (threshold < 17°C) thermosensory receptors in the nasal mucosa, triggering rapid sympathetically mediated vasoconstriction within seconds to minutes. This is followed by reactive vasodilation with ischemia–reperfusion injury, increased capillary permeability, and release of histamine, bradykinin, prostaglandins (PGE₂, PGD₂), leukotrienes (LTC₄, LTD₄), and substance P — collectively producing the clinical triad of rhinorrhea, nasal congestion, and sneezing independently of any viral agent. Mucociliary dysfunction: Cold air reduces nasal mucosal temperature to 15–20°C, decreasing ciliary beat frequency (CBF) by approximately 50% — from 12–15 Hz to 6–8 Hz at 20°C, with near-complete arrest below 10°C. Simultaneously, dehydration of inhaled cold air increases mucus viscosity and reduces elasticity, impairing mucociliary transport. Mucociliary clearance time increases from a normal 10–20 minutes to over 60 minutes, significantly compromising pathogen elimination and epithelial barrier integrity. Metabolic and thermodynamic stress: Original thermodynamic calculations demonstrate that conditioning cold air (0°C) to tracheobronchial conditions (37°C, 100% relative humidity) requires approximately 14.2 W — equivalent to ~18% of basal metabolic rate at rest. During physical exertion (minute ventilation 30–60 L/min) this proportion rises to 25–35%, and under extreme cold (−20°C) may reach 40–50% of basal metabolism. This substantial energetic burden induces local ATP depletion in ciliated epithelial cells, impairs ion pump function (Na⁺/K⁺-ATPase), reduces synthesis of protective proteins (mucins, defensins, lysozyme), and activates pro-inflammatory signaling pathways (NF-κB, MAPK). Neuroendocrine immunosuppression: Cold stress activates the hypothalamic–pituitary–adrenal (HPA) axis, elevating corticotropin-releasing hormone (CRH), adrenocorticotropic hormone (ACTH), and cortisol. Concurrently, sympathetic activation releases noradrenaline and adrenaline, producing a biphasic immunomodulatory effect: transient stimulation followed by sustained suppression of mucosal immunity. Secretory IgA (sIgA) production is reduced through direct suppression of plasma cell function, decreased mucosal blood flow, and HPA-mediated immunosuppression — collectively increasing susceptibility to secondary viral infection. Resolution of the age paradox: The counterintuitive age-related incidence pattern (children > adults > elderly) is explained not by differences in immune competence but by quantitative differences in cold exposure: children spend more time outdoors in cold weather, dress less adequately, have a higher relative minute ventilation per kilogram of body weight, and possess less developed thermoregulatory mechanisms. This host-response model, proposed by Gozhenko et al. (2025), provides a more parsimonious and evidence-consistent explanation than the traditional "accumulated immunity" hypothesis. The synergistic interaction between ACRS and viral infection is also characterized: cold-induced mucociliary dysfunction prolongs viral contact time with the mucosa, epithelial barrier compromise facilitates viral invasion, and neuroendocrine immunosuppression reduces interferon-based antiviral defense — collectively creating conditions that maximally favor viral replication and symptomatic disease. Ten original research problems and ten testable research hypotheses are formulated, including: the TRPM8-mediated vasoconstriction hypothesis (pharmacological blockade as prevention), the metabolic depletion hypothesis (ATP deficit as a measurable biomarker of ACRS), the thermoacclimatization hypothesis (systematic cold hardening as an evidence-based preventive strategy), the microbiome disruption hypothesis, and the neurogenic inflammation hypothesis (substance P and CGRP as primary mediators of symptom onset). Conclusions The "common cold" is not a purely infectious disease but a complex syndrome in which cold stress plays an independent and fundamental pathogenetic role. The term Acute Cold Respiratory Syndrome (ACRS) more accurately reflects the multifactorial etiology of acute upper respiratory tract disorders, encompassing thermal stress, vascular dysfunction, metabolic burden, and immune modulation — with or without concomitant viral infection. The paradigmatic shift from a pathogen-centric to a host-response model, as proposed by Gozhenko et al. (2025), is scientifically justified and supported by convergent evidence from multiple biomedical disciplines. ACRS and viral upper respiratory tract infection are not mutually exclusive but synergistic processes: ACRS acts as a "gateway" that enhances viral susceptibility, while viral infection potentiates the cold-initiated inflammatory response. Recognition of ACRS as an independent nosological entity has significant practical implications: it reframes prevention (active cold protection as a standalone strategy), diagnosis (differentiation of ACRS from viral cold using proposed major and minor criteria), and treatment (warming and mucociliary restoration without antiviral agents in pure ACRS), with the potential to substantially reduce the global socioeconomic burden of one of humanity's most common diseases. Актуальність Гострі респіраторні захворювання, що колективно позначаються терміном «застуда», є одними з найпоширеніших патологій у світі: вони вражають мільярди людей щорічно та спричиняють колосальний соціально-економічний тягар, що перевищує 40 мільярдів доларів на рік лише у США. Попри їх повсюдність, етіопатогенез цих захворювань залишається недостатньо вивченим і науково дискусійним. Сучасна медицина пояснює всі прості простудні епізоди виключно вірусними інфекціями — переважно риновірусами (30–50%), коронавірусами (10–15%) та іншими респіраторними вірусами. Однак ця моноказуальна вірусна парадигма не пояснює низки добре задокументованих клінічних та епідеміологічних невідповідностей: розвиток симптомів протягом хвилин після холодового впливу (задовго до будь-якого можливого інкубаційного періоду), оборотність симптомів після зігрівання, відсутність лихоманки у значній частині випадків та парадоксальна вікова закономірність захворюваності, за якої літні люди — попри прогресивну імуносенесценцію — хворіють рідше, ніж діти та молоді дорослі. Ці невирішені суперечності потребують фундаментального переосмислення патогенезу холодо-асоційованих респіраторних захворювань. Мета Цей наративний огляд критично аналізує роль холодового впливу та холодового стресу в патогенезі гострих захворювань верхніх дихальних шляхів і пропонує нову концептуальну модель — Гострий холодовий респіраторний синдром (ГХРС) — як самостійну нозологічну одиницю з чітко визначеними патофізіологічними механізмами, специфічними діагностичними критеріями та конкретними клінічними імплікаціями. Огляд також обґрунтовує парадигматичний зсув від патоген-центричної до хост-відповідної моделі «застуди», запропонований Gozhenko et al. (2025). Методи Проведено комплексний наративний огляд літератури в базах даних PubMed/MEDLINE, Scopus, Web of Science та Google Scholar, що охоплює публікації за 1946–2025 рр. англійською, українською та польською мовами. Ключові слова для пошуку включали: cold stress, thermoregulation, upper respiratory tract, mucosal immunity, vasoconstriction, common cold pathophysiology, mucociliary clearance, cold air inhalation, HPA axis immune suppression, TRPM8, TRPA1, nasal mucosa cold. Інструменти штучного інтелекту (великі мовні моделі) використовувались виключно для допоміжних завдань — первинного сортування літератури, граматичної перевірки тексту та форматування бібліографічних посилань; увесь науковий зміст, аналіз і висновки є виключно результатом інтелектуальної праці авторів. У рукописі представлено оригінальні термодинамічні розрахунки метаболічних енергетичних витрат при диханні холодним повітрям. Результати Конвергентні дані з фізіології, імунології, нейронауки та термодинаміки розкривають п'ять взаємопов'язаних патофізіологічних механізмів ГХРС: Судинна дисфункція: Вдихання холодного повітря активує термосенсорні рецептори слизової оболонки носа — TRPM8 (поріг < 25–28°C) та TRPA1 (поріг < 17°C) — ініціюючи швидку симпатично-опосередковану вазоконстрикцію протягом секунд–хвилин. Наступна реактивна вазодилатація супроводжується ішемією–реперфузією, підвищенням проникності капілярів та вивільненням гістаміну, брадикініну, простагландинів (PGE₂, PGD₂), лейкотрієнів (LTC₄, LTD₄) і субстанції P — що формує клінічну тріаду ринореї, закладеності носа та чхання незалежно від будь-якого вірусного агента. Мукоциліарна дисфункція: Холодне повітря знижує температуру слизової оболонки носа до 15–20°C, зменшуючи частоту биття війок (ЧБВ) приблизно вдвічі — з 12–15 Гц до 6–8 Гц при 20°C, з практично повним припиненням руху нижче 10°C. Одночасно дегідратація вдихуваного холодного повітря підвищує в'язкість слизу та знижує його еластичність, порушуючи мукоциліарний транспорт. Час мукоциліарного кліренсу зростає з нормальних 10–20 хвилин до понад 60 хвилин, що суттєво компрометує елімінацію патогенів та цілісність епітеліального бар'єру. Метаболічний та термодинамічний стрес: Оригінальні термодинамічні розрахунки демонструють, що кондиціонування холодного повітря (0°C) до умов трахеобронхіального дерева (37°C, 100% відносна вологість) вимагає приблизно 14,2 Вт — що еквівалентно ~18% базального метаболізму у стані спокою. При фізичному навантаженні (хвилинний об'єм 30–60 л/хв) ця частка зростає до 25–35%, а при екстремальному морозі (−20°C) може досягати 40–50% базального метаболізму. Таке суттєве енергетичне навантаження спричиняє локальне виснаження АТФ у клітинах миготливого епітелію, порушує функцію іонних насосів (Na⁺/K⁺-АТФаза), знижує синтез захисних білків (муцинів, дефензинів, лізоциму) та активує прозапальні сигнальні шляхи (NF-κB, MAPK). Нейроендокринна імуносупресія: Холодовий стрес активує вісь гіпоталамус–гіпофіз–наднирники (ГГН), підвищуючи рівні кортикотропін-рилізинг гормону (КРГ), адренокортикотропного гормону (АКТГ) та кортизолу. Одночасна симпатична активація вивільняє норадреналін та адреналін, чинячи двофазний імуномодулюючий ефект: транзиторну стимуляцію з наступним тривалим пригніченням слизового імунітету. Продукція секреторного IgA (sIgA) знижується через пряме пригнічення функції плазматичних клітин, зменшення кровотоку в слизовій оболонці та ГГН-опосередковану імуносупресію — що сукупно підвищує сприйнятливість до вторинної вірусної інфекції. Вирішення вікового парадоксу: Контрінтуїтивна вікова закономірність захворюваності (діти > дорослі > літні) пояснюється не відмінностями в імунній компетентності, а кількісними відмінностями в холодовому впливі: діти проводять більше часу на вулиці в холодну погоду, менш ефективно одягаються, мають вищий відносний хвилинний об'єм дихання на кілограм маси тіла та менш розвинені терморегуляторні механізми. Ця хост-відповідна модель, запропонована Gozhenko et al. (2025), є більш переконливою та узгодженою з наявними доказами, ніж традиційна гіпотеза «накопиченого імунітету». Також охарактеризовано синергетичну взаємодію між ГХРС та вірусною інфекцією: холодо-індукована мукоциліарна дисфункція подовжує час контакту вірусів зі слизовою оболонкою, компрометація епітеліального бар'єру полегшує вірусну інвазію, а нейроендокринна імуносупресія знижує інтерферон-опосередкований противірусний захист — що сукупно створює умови, які максимально сприяють вірусній реплікації та розвитку симптоматичного захворювання. Сформульовано десять оригінальних дослідницьких проблем та десять верифікованих дослідницьких гіпотез, зокрема: гіпотезу TRPM8-опосередкованої вазоконстрикції (фармакологічна блокада як профілактика), гіпотезу метаболічного виснаження (дефіцит АТФ як вимірюваний біомаркер ГХРС), гіпотезу термоадаптації (систематичне загартовування як науково обґрунтована профілактична стратегія), гіпотезу мікробіомної дисрупції та гіпотезу нейрогенного запалення (субстанція P та CGRP як первинні медіатори симптомоутворення). Висновки «Застуда» є не суто інфекційним захворюванням, а складним синдромом, у якому холодовий стрес відіграє самостійну та фундаментальну патогенетичну роль. Термін Гострий холодовий респіраторний синдром (ГХРС) точніше відображає багатофакторну етіологію гострих захворювань верхніх дихальних шляхів, що охоплює термічний стрес, судинну дисфункцію, метаболічне навантаження та імунну модуляцію — з або без супутньої вірусної інфекції. Парадигматичний зсув від патоген-центричної до хост-відповідної моделі, запропонований Gozhenko et al. (2025), є науково обґрунтованим і підтримується конвергентними доказами з різних галузей біомедицини. ГХРС та вірусна інфекція верхніх дихальних шляхів є не взаємовиключними, а синергетичними процесами: ГХРС виступає «воротами», що підвищують вірусну сприйнятливість, тоді як вірусна інфекція потенціює холодо-ініційовану запальну відповідь. Визнання ГХРС самостійною нозологічною одиницею має суттєві практичні імплікації: воно переосмислює профілактику (активний захист від холоду як самостійна стратегія), діагностику (диференціація ГХРС від вірусної застуди за запропонованими великими та малими критеріями) та лікування (зігрівання і відновлення мукоциліарної функції без противірусних препаратів при чистому ГХРС) — з потенціалом суттєво знизити глобальний соціально-економічний тягар одного з найпоширеніших захворювань людства.